Analysis on high throughput layout of container yards. Issue 16 (18th August 2018) - Lee, Byung Kwon; Lee, Loo Hay; Chew, Ek Peng
Abstract : The operational efficiency of handling resources plays an important role in promoting container flows at a container terminal. As these handling resources operate on specific yard layouts, a well-designed layout will promote the performance of the handling activities. This study aims to discuss a design process to maximise the throughput capacity, as well as minimise the resource configuration when designing the yard layout. Various experiments were conducted and analysed to demonstrate the effects on the layout structure and the resource configuration for the two types of parallel yard layouts: the double-lane yard layout where vehicles can access the block at both side and the single-lane yard layout where two adjacent blocks in a row are grouped together and vehicles can access each block at only one side. According to the findings, the container flows by vehicles exert greater influence on the design of a container yard compared to the time taken for container processing by quay cranes and yard cranes. It is also found that the single-lane yard layout is preferable when high throughput capacity is required, whereas the double-lane yard layout is superior in favour of high efficiency of vehicle flows.